Dietary intake of polychlorinated dibenzo-p-dioxins and furans, adiposity and obesity status - Khoury, Nadine; Martínez, María Ángeles; Paz-Graniel, Indira; Martínez-González, Miguel Ángel; Corella, Dolores; Castañer, Olga; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (Environmental research, 2023)
The principal source of exposure to Polychlorinated dibenzo-p-dioxins and polychlorinated dibenzo-p-furans (PCDD/Fs) in humans comes from food intake. PCDD/Fs, are a family of potential endocrine disruptors and have been associated with different chronic diseases such as diabetes and hypertension. However, studies assessing the relationship between dietary exposure to PCDD/Fs and adiposity or obesity status in a middle-aged population are limited. To assess cross-sectionally and longitudinally the associations between estimated dietary intake (DI) of PCDD/Fs and body mass index (BMI), waist circumference, and the prevalence/incidence of obesity and abdominal obesity in a middle-aged population. In 5899 participants aged 55–75 years (48% women) living with overweight/obesity from the PREDIMED-plus cohort, PCDD/Fs DI was estimated using a 143-item validated food-frequency questionnaire, and the levels of food PCDD/F expressed as Toxic Equivalents (TEQ). Consequently, cross-sectional and prospective associations between baseline PCDD/Fs DI (in pgTEQ/week) and adiposity or obesity status were assessed at baseline and after 1-year follow-up using multivariable cox, logistic or linear regression models. Compared to participants in the first PCDD/F DI tertile, those in the highest tertile presented a higher BMI (β-coefficient [confidence interval]) (0.43kg/m2 [0.22; 0.64]; P-trend <0.001), a higher waist circumference (1.11 cm [0.55; 1.66]; P-trend <0.001), and a higher prevalence of obesity and abdominal obesity (1.05 [1.01; 1.09] and 1.02 [1.00; 1.03]; P-trend = 0.09 and 0.027, respectively). In the prospective analysis, participants in the top PCDD/F DI baseline tertile showed an increase in waist circumference compared with those in the first tertile after 1-year of follow-up (β-coefficient 0.37 cm [0.06; 0.70]; P-trend = 0.015). Higher DI of PCDD/Fs was positively associated with adiposity parameters and obesity status at baseline and with changes in waist circumference after 1-year of follow-up in subjects living with overweight/obesity. Further large prospective studies using a different population with longer follow-up periods are warranted in the future to strengthen our results. [Display omitted] •The 87% of our population exceeded the PCDD/Fs levels established by the EFSA.•Red meat, ﬁsh and seafood and fruits and vegetables contributed the most to the PCDD/F dietary intake.•Dietary intake of PCDD/Fs was associated with adiposity and obesity status at baseline.•Higher PCDD/Fs dietary intake was associated with an increase in waist circumference after 1-year of follow-up.